Audit Evaluasi Pemanfaatan Sistem Informasi Akademik di Universitas Kristen Wira Wacana Sumba Menggunakan Framework Cobit 5 - Mira, Trisari D. N. B.; Sediyono, Eko; Iriani, Ade (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Wira Wacana Christian University Sumba in supporting its activities as an educational institution is required to use the Academic Information System. Having an academic information system like the web-based Ecampuz certainly requires auditing, monitoring and evaluation of its performance so that the services produced continue to show good quality. The aim of this research is to evaluate and audit system by using Cobit 5 frameworks, while testing and measuring website quality is using the Apache Jmeter tool. The Cobit5 processes used are: Risk Optimization (EDM03), Security Management (APO13), Risk Management (APO12), Change Management (BAI06), Operations Management (DSS01), Service Requests (DSS02), Troubleshooting (DSS03), Security Services (DSS05), Work Monitoring and Evaluation (MEA01), Internal Control of Monitoring and Evaluation (MEA02). Gap analysis and Maturity Level are aimed at obtaining Audit results with good maturity. The results obtained from the average value based on the gap analysis of 10 Cobit5 processes is 1.2 and the Apache Jmeter test shows throughput of 101.746/minute and Deviation is 3671.